2017
DOI: 10.21163/gt_2017.121.11
|View full text |Cite
|
Sign up to set email alerts
|

Different approaches to defining metropolitan areas (Case study: cities of Brno and Ostrava, Czech Republic)

Abstract: ABSTRACT:The definition and delimitation of metropolitan areas has been the focus of many geographers and other specialists for quite a few decades. The complexity and diversity of the methods and techniques used, and the differing attitudes of those working in this area have brought considerably different, and often controversial, results. The EU has introduced a tool, Integrated Territorial Investments (ITI), to support study in this area by motivating EU member states to define their metropolitan areas. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In today's era of globalization, it is confirmed that creativity and innovation are the driving force of a creative economy. Organizations, regions, cities and urban agglomerations use creativity to generate significantly higher revenues and ensure greater stability in the future (Tonev et al, 2017). Creative economics (including various sustainable and smart aspects) is unique in that it relies on an unlimited resource, ie human creativity, which also gives rise to a significant multidimensional approach to studying changes in the context of economic, geographical, demographic, cultural or social (Van der Pol, 2007;Ponzini & Rossi, 2010;Turón & Gomis, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In today's era of globalization, it is confirmed that creativity and innovation are the driving force of a creative economy. Organizations, regions, cities and urban agglomerations use creativity to generate significantly higher revenues and ensure greater stability in the future (Tonev et al, 2017). Creative economics (including various sustainable and smart aspects) is unique in that it relies on an unlimited resource, ie human creativity, which also gives rise to a significant multidimensional approach to studying changes in the context of economic, geographical, demographic, cultural or social (Van der Pol, 2007;Ponzini & Rossi, 2010;Turón & Gomis, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The issue of the definition of metropolitan areas is taken up by Tonev et al (Tonev et al 2017), who investigate the methodological approaches related to the functional integration of regional units and inter-regional relations. They focus on those used within Integrated Territorial Investments (ITI) to delimit the metropolitan areas analyzing the functional integration of regional units and inter-regional relations.…”
Section: The Traditional Use Of Aggregation Thresholdsmentioning
confidence: 99%
“…Frýdek-Místek, a town of 55,931 people [61], belongs to the important urban centre located in a rapidly developing industrial area with many newly established foreign direct investments in the field of the automotive industry (e.g., Hyundai and other automotive suppliers), on the southern outskirts of Ostrava metropolitan region [62], in the east of Czechia, close to the border with Poland.…”
Section: Study Areamentioning
confidence: 99%